Sustaining strength–ductility synergy of CoCrFeNiMn high entropy alloy by a multilevel heterogeneity associated with nanoparticles. (October 2020) - Xie, Yuehuang; Liang, Jiamiao; Zhang, Deliang; Luo, Yifei; Zhang, Zhen; Liu, Yu; Wang, Jun
Abstract: A high tensile yield strength of 1298 MPa and good ductility (uniform elongation: 9.4%) of CoCrFeNiMn high entropy alloy can be sustained by a multilevel structural heterogeneity facilitated by ultrafine grained regions (UFGRs), coarse grained regions (CGRs) and a non-uniform dispersion of TiO(C) nanoparticles in UFGRs. Analysis reveals that the Young's modulus difference and strain gradient associated with the nanoparticles enhance the back stress. Meanwhile, forward stress was estimated quantitatively, which further suggests that nanoparticles also effectively increase resistance to the forward stress, leading to a better strength–ductility synergy than a simple heterogeneous structure with only UFGRs and CGRs. Graphical abstract: Image, graphical abstract